2013
DOI: 10.1093/qjmed/hct072
|View full text |Cite
|
Sign up to set email alerts
|

A study into efficacy of omalizumab therapy in patients with severe persistent allergic asthma at a tertiary referral centre for asthma in Ireland

Abstract: Overall, responders to omalizumab therapy are less likely to experience an asthma exacerbation and hospitalization. They were also more likely to reduce maintenance corticosteroid therapy and the need for rescue reliever therapy. These data suggest that omalizumab has proven effective in improving health outcomes for a cohort of carefully selected patients with severe allergic asthma in Ireland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…To minimize bias, non-significant results reported in the original publication were included in our pooled estimates. Table 1 summarizes the 42 studies stratified by 30 adult-only studies [24,26,27,[30][31][32][33][34][35][36][37][40][41][42][43][44][45][46][47][58][59][60][61][62][63][64][65][66][67][68] (n = 3558) and 12 adult/ adolescent studies [25,38,39,56,57,[69][70][71][72][73][74][75][76][77] (n = 5819). These 42 studies comprised a total of 9377 patients from 35 countries: 25 in Europe (incl.…”
Section: Other Methodological Considerationsmentioning
confidence: 99%
“…To minimize bias, non-significant results reported in the original publication were included in our pooled estimates. Table 1 summarizes the 42 studies stratified by 30 adult-only studies [24,26,27,[30][31][32][33][34][35][36][37][40][41][42][43][44][45][46][47][58][59][60][61][62][63][64][65][66][67][68] (n = 3558) and 12 adult/ adolescent studies [25,38,39,56,57,[69][70][71][72][73][74][75][76][77] (n = 5819). These 42 studies comprised a total of 9377 patients from 35 countries: 25 in Europe (incl.…”
Section: Other Methodological Considerationsmentioning
confidence: 99%
“…Other anti-asthmatic treatments, both prior to and after start of omalizumab treatment, were included in twelve of these studies (28, 30-33, 35, 37, 42, 44, 45, 48, 49). The most common clinical outcome, included in 14 studies, was FEV1 (28,32,34,35,37,39,42,43,(45)(46)(47)(48)(49)(50). Fewer studies reported on other objective (32,34,39,46,49,50) and subjective (29,41) (37,42,50)), and work or school days lost due to asthma (29,32,37,44).…”
Section: Study Designsmentioning
confidence: 99%
“…Hence, the majority of patients can be estimated to have ranged from about 25 to 70 years of age -covering the predominant adult population. There was a slight preponderance of female patients: there were proportionately more women in 20 of the 23 studies reporting gender distribution (27)(28)(29)(30)(31)(32)(33)(34)(35)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). The majority of patients weighed between 66 kg (44) and 81 kg (45) Omalizumab candidates presented with marked one-year histories of severe exacerbations.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our SLR identified 83 primary studies with epidemiology data relevant to SUA; all were observational studies. Three studies were international (involving multiple countries from different continents) [11][12][13] , and the remaining studies were from Asia [14][15][16][17][18][19] , Australia 20,21 , Germany 22,23 , France [24][25][26][27] , Italy [28][29][30][31][32][33][34][35] , Spain 36-40 , the UK 6,[41][42][43][44][45][46][47][48] , Europe (other) [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]…”
Section: Epidemiology Of Asthma Uncontrolled By Gina Steps 4 or 5 Trementioning
confidence: 99%